Are tidal lagoons ecologically relevant to larval recruitment of small pelagic fish? An approach using nutritional condition and growth rate - Chicharo, Maria Alexandra (2013)
There are numerous studies dealing with larvae of Small Pelagic Fish (SPF), but only a few have actually addressed advanced larval phases. Temperate coastal lagoons are particularly understudied, due to the absence of standard method to capture advanced larval fish in these near shore shallow habitats. Accordingly, this study aims to describe abundances, nutritional condition and in situ growth of postflexion (SPF) from the Ria Formosa, a tidal coastal lagoon in southern Portugal. The nutritional condition and in situ growth were determined through cohort analysis and standardized RNA:DNA ratio (sRD), complemented with feeding incidence (gut content) and fatty acids (FAs, trophic biomarkers) of postflexion larvae sampled sequentially with light traps, from spring 2005 to summer 2006. Simultaneously, environmental parameters such as water temperature, salinity, dissolved oxygen and chlorophyll a were measured. Post-larvae of SPF were captured through the year in important numbers. The dominant species were Sardina pilchardus (50.7%), Engraulis encrasicolus and Atherina presbyter (11.4%). These results are distinct from those based on adult/juvenile surveys or early planktonic phases in the Ria Formosa where clupeiformes were occasionally reported. Sardines were captured mainly in winter, spring and early summer and anchovies mainly during summer and autumn. Sand smelt, a resident species, was present throughout the year. In the early summer, the three species were present and during this period some diet overlapping occurred, the feeding incidence of the clupeiformes was very low, but atherinids always exhibited full guts reflecting the different gut morphology or indicating different lifecycle strategies. The bulk of the diet was mollusks, crustaceans and appendicularians, for sand smelts, sardines and anchovies, respectively. The results of FA analyses showed some contribution of phytoplankton to SPF in the area. All SPF exhibited higher condition (sRD) and growth rates in summer, which are explained by the adequate temperature and higher planktonic productivity. This is especially relevant because the successful development of postflexion larvae in these nursery areas largely determines the successful recruitment to adult fish populations.